Effects of NaCl on Root Growth and Cell Wall Composition of Two Soya bean Cultivars with Contrasting Salt Tolerance. Issue 3 (June 2014) - An, P.; Li, X.; Zheng, Y.; Matsuura, A.; Abe, J.; Eneji, A. E.; Tanimoto, E.; Inanaga, S.
Abstract Our objectives were to determine the influence of salinity on root cell wall composition in soya beans and the possible mechanism of salt tolerance. Two soya bean cultivars, Touzan 69 (salt sensitive) and Dare (salt tolerant), were selected as experimental material for comparison. Root growth was clearly inhibited by salinity in both cultivars, but Touzan 69 showed more severe reductions in root length than Dare. In the 0–5 mm root segment (from root tip), the total cell wall sugar content of Touzan 69 decreased considerably due to salinity as were the pectin, hemicellulose and cellulose fractions. In Dare, NaCl treatments only caused a slight decrease in the pectin fraction and no marked change in hemicellulose and cellulose fractions. Without salt treatment, the pectin fraction accounted for about 40 % and cellulose for 30 % of cell wall composition in the 0–5 mm root segment; in the 5–10 segment (from root tip), pectin and cellulose accounted for 27 % and 45 % in Touzan 69, and 34 % and 38 % in Dare. The percentage of pectin decreased and that of cellulose increased in the 5–10 mm root segment compared with the 0–5 mm segment. This indicates that pectin largely regulates cell growth, as the 0–5 mm region is considered the elongation zone of soya bean roots. Salt treatment decreased the percentage of pectin, but increased that of cellulose across root zones of the two cultivars, suggesting that salt presence may increase cell wall rigidity, and thus, inhibits root growth. Dare was able to maintain its main root cell wall substances, an apparent advantage for root cell growth that may overall improve its salt tolerance. Also, the less reduction in cell wall uronic acid was of some benefit in the positive regulation of root cell growth in Dare. The changes in cell wall composition, especially the pectin content had a close relation with the regulation of root growth. The difference in salt tolerance between the two tested cultivars can partly be explained on the basis of these changes in response to salinity. Sugar compounds in each cell wall constituent and their functions in ion transport as well as the relationship between root cell wall and soya bean salt tolerance need to be further investigated.